Chaos game optimization for extracting global MPP of PV System based high-efficiency triple-junction solar cell - Houssam Eddine Ghadbane; Hegazy Rezk; Aissa Benhammou; Ahmed F. Mohamed (Results in Engineering)
High-efficiency triple-junction solar cells (TJSC) have received more attention in concentrated solar photovoltaic (PV) systems because of their ultimate feathers. In this paper, chaos game optimization (CGO) is used for extracting the global maximum power point (MPP) of high efficiency InGaP/InGaAs/Ge TJSC based PV system considering partial shading (PS). With PS, the power versus voltage characteristics comprises some local MPPs and unique global ones. Consequently, traditional MPP tracking approaches cannot discriminate between global and local points and are always stuck with local MPP. In this case, the PV power is reduced, and hence, an optimization algorithm such as CGO is highly required to mitigate the PCS of the PV system. To prove the dependability of CGO in extracting the global MPP, four PS patterns are used to test the superiority of CGO in cases of changing the position of the global MPP. A comparison with another optimzation algorithms also considered and the results confirmed the superiority of CGO compared with other algorithms. As an example, in the first PS pattern, the average PV power levels were between 865.67 W and 993.89 W. The maximum power that CGO can achieve is 993.89 W whereas when using COOT, the lowest power output is 865.67 W. In addition, CGO achieves the lowest STD of 0.032.